Description of Sectonema septentrionale sp. n. (Nematoda: Dorylaimida: Aporcelaimidae) from Northern Iberian Peninsula - Peña-Santiago, Reyes; Álvarez-Ortega, Sergio (Zootaxa, 2015)
A new species of the genus Sectonema, collected from natural forests in the Spanish provinces of León and Palencia, is described and illustrated with line drawings and LM pictures. Sectonema septentrionale sp. n. is characterized by its 5.59–6.90 mm long body, lip region 25–29 μm broad and offset by deep constriction, mural tooth 18–19 μm long at its ventral side and occupying most of the stomatal lumen, pharyngeal expansion 618–926 μm long or 60–73% of total neck length, uterus tripartite and 370–493 μm long or 2.9–4.3 times the corresponding body diameter, V = 48–52, tail short and rounded (40–62 μm, c = 108–146, c’ = 0.6–0.8), spicules 100–145 μm long, and 5–11 irregularly spaced ventromedian supplements with hiatus. It is very close to S. demani, but differs both in the nature of the mural tooth and of the uterus.